Faktor-Faktor yang Mempengaruhi Terjadinya Intensi Turnover Pada Karyawan PT BAN Indonesia - Asep Gunawan (JBIMA (Jurnal Bisnis dan Manajemen), 2016)
The purpose of this study was intended to find answers to the problems potentially increasing turnover intention in PT BAN Indonesia, which is associated with the issue of group cohesiveness, job stress, and job satisfaction. The results showed that the group cohesiveness variable (X1) and job satisfaction variables (X3) negatively affect the level of turnover intention, with the t value of -3.865 X1 and X2 at -4.285. Variable Work Stress (X2) has positive influence on the level of turnover intention with the t value X2 by 5,423.